2018
DOI: 10.1121/1.5027410
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation to foreign-accented speech and its transfer to an unfamiliar talker

Abstract: How fast can listeners adapt to unfamiliar foreign accents? Clarke and Garrett [J. Acoust. Soc. Am. 116, 3647-3658 (2004)] (CG04) reported that native-English listeners adapted to foreign-accented English within a minute, demonstrating improved processing of spoken words. In two web-based experiments that closely follow the design of CG04, the effects of rapid accent adaptation are examined and its generalization is explored across talkers. Experiment 1 replicated the core finding of CG04 that initial perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…For instance, listeners rapidly get attuned to the speech of unfamiliar L2 speakers, often requiring just over a minute of experience (Clarke & Garrett, 2004). Xie et al (2018) recently extended these findings to show that listeners improve quickly (in a matter of minutes) in speed and accuracy of comprehension of unfamiliar L2 speakers, arguing that long-and short-term adaptations to L2 speech might be driven by similar mechanisms. Our finding of a rapid convergence in interlocutors' comprehensibility ratings, which generally occurred within 1-3 minutes of their experience in the initial task (see Figure 3), is suggestive of a parallel phenomenon for comprehensibility.…”
Section: Between-speaker Alignment In Comprehensibilitymentioning
confidence: 90%
“…For instance, listeners rapidly get attuned to the speech of unfamiliar L2 speakers, often requiring just over a minute of experience (Clarke & Garrett, 2004). Xie et al (2018) recently extended these findings to show that listeners improve quickly (in a matter of minutes) in speed and accuracy of comprehension of unfamiliar L2 speakers, arguing that long-and short-term adaptations to L2 speech might be driven by similar mechanisms. Our finding of a rapid convergence in interlocutors' comprehensibility ratings, which generally occurred within 1-3 minutes of their experience in the initial task (see Figure 3), is suggestive of a parallel phenomenon for comprehensibility.…”
Section: Between-speaker Alignment In Comprehensibilitymentioning
confidence: 90%
“…We note that having a sufficient sample to provide substantial evidence for H1/H0 using Bayesian methods, or to obtain 90% power for frequentist methods, would likely require a much larger sample than is standard in these types of studies. Given the time-consuming nature of these multiple session training studies, moving to online testing may be necessary to make this feasible (see Xie et al, 2018 for an example of an acoustic training study done over the web), or alternately multi-lab collaboration may be necessary. Note that this would also allow us to see whether the fact that Perrachione et al, (2011) found their interaction with untrained voices, whereas Sadakata & McQueen (2014) found it only for trained voices, is a true difference (due to the different paradigms) or due to power.…”
Section: Discussionmentioning
confidence: 99%
“…We find that subtitles facilitate native language accent adaptation with far less exposure than in used in previous work on second language accent learning (approximately 45 seconds of speech input, compared to 30 minutes in [ 40 ]). This suggests that a small amount of exposure material is sufficient to investigate maintenance (see also [ 38 , 50 ]). Next, we discuss considerations for future research on information maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that despite this variability, web-based experiments on speech perception are feasible [ 45 – 47 ]. This includes studies on accent adaptation [ 48 50 ]. To reduce the between-speaker variability, we required participants to use either in-ear or over-ear headphones when taking the experiment.…”
Section: Methodsmentioning
confidence: 99%